Challenges for women's leadership in organisations, from the perspective of judge and prophetess Deborah - J.A. Triana Palomino; I.D. Toro-Jaramillo; S.M. Giraldo Sánchez (Acta Theologica)
This article presents a contextual and biblical approach to the phenomenon of women’s low participation in topmanagement positions. Studies show that the difficulties women face in organisations are related to biases that assume a natural inferiority of women compared to men. These biases have uncritically been assimilated into the culture, including the work environment, and to overcome them, it is necessary to create scenarios of individual and collective confrontation, in order to recognise women’s capacity to exercise authority and power. The biblical narrative of judge and prophetess Deborah and her editorial process in the 8th century BC provide clues for confrontation and transformation by naturally portraying a woman exercising authority in a patriarchal setting, relating to men on an equal footing, and being recognised and respected through attitudes of listening, care, and empathy.